Budaya Literasi Di Pondok Pesantren Al-Falah Putri Sumber Gayam - Suaidah, Suaidah (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Literacy culture plays a crucial role in improving the reading and writing skills of female students at Pondok Pesantren Al-Falah Sumber Gayam. This study aims to explore the implementation of literacy activities, understand the challenges faced, and assess the positive impact on the students. The research employs a descriptive qualitative method, collecting data through interviews, observations, and documentation. The findings reveal that literacy activities such as reading classical Islamic texts, discussions, and writing scientific papers have successfully enhanced the students' reading interest and writing skills, despite several challenges like limited resources and time constraints. The scientific contribution of this research is expected to provide insights for the development of literacy programs in pesantren and other educational institutions, while promoting the importance of literacy in shaping students' character.